La enfermedad de la caida de la fruta en citricos - Del Rivero, J.M.
(Es, En)
ilus., 13 ref.
Keywords: CITRUS; GLOMERELLA CINGULATA; EPIDEMIOLOGIA; ANTRACNOSIS; CAIDA PREMATURA DE LOS FRUTOS; CONTROL QUIMICO; BENOMILO; TIABENDAZOL; COBRE; CUARENTENA; ESPAÑA